2022
DOI: 10.1353/cpr.2022.0035
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Information Sources for Black and Latine Communities: A Community Co-created Survey

Abstract: he coronavirus disease 2019 (COVID-19) pandemic disproportionately impacts Black and Latine communities, who are experiencing health and economic ramifications of the pandemic at higher rates compared with non-Hispanic white communities. [1][2][3][4][5][6][7] Ensuring equitable access to the COVID-19 vaccine is critical to reducing these disparities and improving health. Mistrust of medical professionals, research institutions, and governmental agencies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…We also found that participants had the least trust in their social media contacts and faith leaders for COVID-19 information, which also aligns with the findings of Ragavan et al [19], which found that while social media trust was low, there was high utilization of social media channels, with 72% of their participants reporting use of Facebook as a source of information-higher than any other source asked about in the study. In our study, 34% of all participants reported putting a great deal of trust in faith leaders.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that participants had the least trust in their social media contacts and faith leaders for COVID-19 information, which also aligns with the findings of Ragavan et al [19], which found that while social media trust was low, there was high utilization of social media channels, with 72% of their participants reporting use of Facebook as a source of information-higher than any other source asked about in the study. In our study, 34% of all participants reported putting a great deal of trust in faith leaders.…”
Section: Discussionsupporting
confidence: 90%
“…Our research question was conceptualized through discussion of another study our team was conducting examining Black and Latine adults’ perspectives on COVID-19 vaccines. 26 Our team noted how this work was important but also perpetuated burdening communities with surveys rather than understanding researchers' perspectives. Therefore, a small group from the trustworthiness workgroup convened to conduct this study.…”
Section: Methodsmentioning
confidence: 99%
“…Community-partnered research is a unique approach in which researchers and community members engage in the scientific process together. [21][22][23][24] This method dismantles traditional power structures, assumptions around scholarly and experiential knowledge, and emphasizes research reciprocity and the amplification of community priorities. 25,26 Our team has worked closely together throughout the COVID-19 pandemic within the Community Vaccine Collaborative (CVC), which is a community-academic partnership focused on promoting vaccine equity.…”
mentioning
confidence: 99%